If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -4 + 4x + -2 = 7x Reorder the terms: -4 + -2 + 9x + 4x = 7x Combine like terms: -4 + -2 = -6 -6 + 9x + 4x = 7x Combine like terms: 9x + 4x = 13x -6 + 13x = 7x Solving -6 + 13x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -6 + 13x + -7x = 7x + -7x Combine like terms: 13x + -7x = 6x -6 + 6x = 7x + -7x Combine like terms: 7x + -7x = 0 -6 + 6x = 0 Add '6' to each side of the equation. -6 + 6 + 6x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 6x = 0 + 6 6x = 0 + 6 Combine like terms: 0 + 6 = 6 6x = 6 Divide each side by '6'. x = 1 Simplifying x = 1
| -2x+49=-9x | | 11(c-5)+5=4+c-54 | | (x-(3-4i))(x-(3+4i))=0 | | X*x-50=0 | | 4x+7=21x-1 | | 4x^3+6x^2-12x-4=0 | | 4(c+7)=4(c-2) | | (-2.2)7x-4=(-2.2)8x+3 | | 0=-12y | | 6+2x=7-x | | 2x^3-8x^2-64x-55296=0 | | -180=-4(6n+3) | | 20-7b=-66+21 | | 3x^2-9x=-5x-5 | | 3n+4.5-n=10.5 | | 14(14y+10)= | | 4(2x-3)-7(x-2)= | | (-2.9)8x-1=(-2.9)9x+4 | | 5z-8=33 | | x-24=-36 | | -7(6-4b)=98 | | h(x)=X^4-2x^3+14x^2+6x-51 | | (6x-3)+7=44 | | 9(21-1x)=17(2x+1) | | 3z+11+28z=50+29z-(-1) | | 4y-19y=60 | | -(4x+3)-(-3x-5)=3 | | 5x-4=5(2x-3) | | 10x-1(3x-2)=30 | | 2(x-3)=3y | | -5(4y-5)+20y= | | -4+3n=4(n+2) |